Digital Twin Integration Analysis for Overall Equipment Effectiveness (OEE) Improvement in Smart Manufacturing Environments - Djehutihotep Wahibremesu (IHSA Institute, 2026)
Manufacturing industries are increasingly adopting Digital Twin technology as part of Industry 4.0 initiatives to enhance operational efficiency, productivity, and competitiveness in rapidly evolving industrial environments. Despite advancements in manufacturing technologies, many organizations continue to face challenges such as unplanned machine downtime, inefficient maintenance practices, reduced production performance, and quality-related losses, all of which negatively affect Overall Equipment Effectiveness (OEE). This study aims to analyze the impact of Digital Twin integration on OEE improvement within manufacturing systems. A quantitative case-study approach was employed using machine operational data, production records, maintenance reports, and real-time sensor information collected from a manufacturing environment. The study compared OEE values before and after the implementation of Digital Twin technology through descriptive, comparative, and statistical performance analyses. The Digital Twin system integrated real-time monitoring, predictive maintenance, and process optimization capabilities by creating a virtual representation of physical production assets synchronized with operational data. The results revealed significant improvements across all OEE dimensions. Availability increased from 75% to 88% due to the reduction of unplanned downtime through predictive maintenance, while Performance improved from 82% to 91% as a result of enhanced process monitoring and operational optimization. Quality increased from 90% to 95% through improved process control and early detection of production anomalies. Consequently, overall OEE improved substantially from 55.35% to 76.08%. Furthermore, Digital Twin integration serves as a strategic enabler of smart manufacturing and Industry 4.0 transformation, contributing to increased productivity, operational excellence, and sustainable industrial development.